2011
DOI: 10.1177/1354856510394604
|View full text |Cite
|
Sign up to set email alerts
|

Invisible Whispers: Accounts of SMS Communication in Shared Physical Space

Abstract: The use of short message services (SMS) on mobile phones has gained huge popularity in most western and many developing countries — so much so that it has become established as the preferred medium for mobile communication especially among young people. This article explores SMS as used for discreet communication between people in the same physical space (‘shared physical space SMS’ — or ‘SPS-SMS’). Drawing from semi-structured interviews with young people in Norway, 10 different scenarios of SPS-SMS use are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 70 publications
(42 reference statements)
1
24
0
3
Order By: Relevance
“…As such, it makes sense to analyse third-place or second-place aspects as situational and physically overlapping. Hence, the 'café-as-laptop-workspace' may serve the function of a physical third place, but at the same time serve as a second place (work) through the laptop workers' digital layers of communication (Tjora, 2011): Many second-place layers of digitally distributed work co-exist with the physical third-place layer of feeling at home within the constant buzz of specific cafés.…”
Section: Discussion: Situational Domesticationmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it makes sense to analyse third-place or second-place aspects as situational and physically overlapping. Hence, the 'café-as-laptop-workspace' may serve the function of a physical third place, but at the same time serve as a second place (work) through the laptop workers' digital layers of communication (Tjora, 2011): Many second-place layers of digitally distributed work co-exist with the physical third-place layer of feeling at home within the constant buzz of specific cafés.…”
Section: Discussion: Situational Domesticationmentioning
confidence: 99%
“…However, when network researchers look more closely into the phenomenon, they also find an opposite trend (Hampton et al, 2010): Actively using a computer and the Internet creates opportunities for creating a wider network of weak ties, with increased social participation as a potential result. Wi-Fi allows us to avoid ever disconnecting from "home" in an emotional and social way (Turkle 2011: 156), within communicative layers (Tjora, 2011) separated from physical social interaction. With the introduction of 3G/4G mobile Internet connections, a large part[footnote-1] of the population in Norway is constantly online.…”
Section: Being Online In Public Placesmentioning
confidence: 99%
“…In each case, psychological distance is being intentionally manipulated. Tjora (2011) It should also be noted that perceived psychological distance may influence the type of digital communication one uses. For instance, in a series of experiments, Amit et al (2012) found that when communicating with someone who is proximal (temporally, socially, or geographically), people tend to prefer using pictures, whereas they tend to prefer using words when the other person is distant.…”
Section: Hypothesis 3: the Use Of Digital Communication May Sometimesmentioning
confidence: 99%
“…Rettie (2009: 427) described this as one area being the 'front region of one performance and the back region of another'. Tjora's (2011) term 'communicative transparency layer' is pertinent to our discussion of participation in online forums. Online forums can be observed anonymously, or participants can jump in and interact with others.…”
Section: Observation Without Informed Consentmentioning
confidence: 99%